The effect of Pr addition on superconducting and mechanical properties of Bi-2212 superconductors - Öztürk, Özgür; Aşıkuzun, Elif; Erdem, Mustafa; Yıldırım, Gürcan; Yıldız, O.; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2011)
In this work, the effects of Pr doping on the superconducting, structural and mechanical properties of the samples are analyzed. Pr doped Bi-2212 superconductors are obtained using solid state reaction method. Dc resistivity measurements are made to investigate the superconducting properties, microhardness measurements are made to analyze the mechanical properties, XRD and SEM measurements are done for crystal structure determination and calculation of the lattice parameters. Using EDS measurements, the change in the elemental composition with doping is analyzed. The Vickers microhardness is calculated for undoped and doped samples. The experimental results of the microhardness measurements are analyzed using Kick’s Law, PSR (proportional specimen resistance), modified PRS (MPSR) and Hays–Kendall (HK) approach. The microhardness values of the samples decrease with Pr addition. The results can be successfully explained by HK approach.